Pleuroperitoneal Leak Complicating Peritoneal Dialysis: A Case Series. (17th August 2011) - Kennedy, C.; McCarthy, C.; Alken, S.; McWilliams, J.; Morgan, R. k.; Denton, M.; Conlon, P. J.; Magee, C.
Abstract : Pressure related complications such as abdominal wall hernias occur with relative frequency in patients on peritoneal dialysis. Less frequently, a transudative pleural effusion containing dialysate can develop. This phenomenon appears to be due to increased intra-abdominal pressure in the setting of congenital or acquired diaphragmatic defects. We report three cases of pleuroperitoneal leak that occurred within a nine-month period at our institution. We review the literature on this topic, and discuss management options. The pleural effusion resolved in one patient following drainage of the peritoneum and a switch to haemodialysis. One patient required emergency thoracocentesis. The third patient developed a complex effusion requiring surgical intervention. The three cases highlight the variability of this condition in terms of timing, symptoms and management. The diagnosis of a pleuroperitoneal leak is an important one as it is managed very differently to most transudative pleural effusions seen in this patient population. Surgical repair may be necessary in those patients who wish to resume peritoneal dialysis, or in those patients with complex effusions. Pleuroperitoneal leak should be considered in the differential diagnosis of a pleural effusion, particularly a right-sided effusion, in a patient on peritoneal dialysis.